Natural course of hepatic focal nodular hyperplasia from childhood to adulthood and review of the literature - Gürses, Cemil; Okşar, Feyzan Seher; Erol, Bekir; Yalçın, Mustafa; Kahvecioğlu, Nevfel; Alparslan, Ahmet Şükrü (Turkish Journal of Gastroenterology, 2017)
Abstract Focal nodular hyperplasia (FNH) is the second most common benign tumor of the liver and constitutes 4% of all primary hepatic tumors in pediatric population. Imaging characteristics of FNH in adults are well known, but those in children have rarely been reported. Here we describe the natural course of a giant hepatic FNH, which was followed up from childhood to adulthood for 12 years using computed tomography (CT) imaging and liver enzyme tests (LET). Differences in CT imaging characteristics were demonstrated. Changes were found in the FNH size in CT images and they were correlated with LET findings. The regression of FNH in our case was compared with the findings in the literature. Hepatic capsular retraction was observed in a benign focal liver lesion in the medical literature for the first time. Cite this article as: Gürses C, Okşar FS, Erol B, Yalçın M, Kahvecioğlu N, Alparslan AŞ. Natural course of hepatic focal nodular hyperplasia from childhood to adulthood and review of the literature. Turk J Gastroenterol 2017; 28: 492-7.